Factors influencing the adoption of microenterprises and their impact in rural Guatemala - Gennrich, Nicolas (2004)
There is a growing consensus that non-agricultural income represents an important source for household support in rural areas, as the resources from agricultural production are insufficient. One wonders to what extent microenterprises (MEs) help to fight poverty and what factors motivate households to form an ME. The present investigation was carried out in El Quiché, Guatemala, a province very affected by extreme poverty, malnutrition and disintegration, due to the civil war that lasted 36 years. It is found that ME is the most significant factor in household income, but unlike what is expected, its effect on housing and nutrition is limited. Regarding the significant factors in the decision to form a ME, they include human capital, social capital, types of crops and market access. The work also explores the effect of collective activities, such as commercialization, on the development of the ME, since the implementation of fairs and community stores contributes considerably to the reduction of transaction costs and the expansion of the market.